Studying the evidence in the concept of group in Roy's adaptation model - María Vilaní Cavalcante Guedes; Marcos Venícios de Oliveira Lopes; Thelma Leite de Araujo (Universidad de Alicante, 2012)
The aim of our study has been the evaluation of the concept of 'group' in Roy's Adaptation Model, taking as basis the inner criterium for evidence suggested by Barnum (1998) in her theoretical analysis pattern. The concept of 'group' is here debated, according to various authors as well as that described by Roy in her different adaptation ways. Our position is that the concept of 'group' in the diverse adaptation models has been adversely affected and that a better description of the Theoretical Model studied should be done especially in the functions of 'role' and 'inter-dependency'.